Integral and Integrated Principles: Alternative Solutions to Overcome the Dichotomy of Islamic Education in Indonesia - FAJRI, Encep Muhammad (PT Batara Swastika Harati, 2025)
Education is currently experiencing a decline due to the frequent imbalance between general education and religious education, especially Islamic religion, resulting in the emergence of educational dichotomy. This research was made with the aim of examining and understanding the dichotomy problems that occur in Indonesia. The type of research used is qualitative using literature review, while the method used is the documentation method. So it can be explained that the dichotomy of education is a problem that is considered quite complicated because the dichotomy of education that is now happening in Indonesia has spread to various educational sectors. The historical roots of this dichotomy began with the entry of Dutch colonizers into Indonesia and changed the existing education system. On the basis of these problems, a solution is needed to overcome the dichotomy of education. The integral and integrated principle is the right solution in overcoming this problem, which with this principle can provide harmony between religious and general sciences.